2019
DOI: 10.2174/1871520619666190705151542
|View full text |Cite
|
Sign up to set email alerts
|

ESM-1: A Novel Tumor Biomaker and its Research Advances

Abstract: Background: Cancer kills nearly 9,000,000 people worldwide, and its mortality was reported up to 28% in the past decade. Few available tumor markers have been known to help early stage diagnosis. In this study, Endocan was taken as a novel tumor marker, which has been found in many cancers related to cancer cell proliferation, neoangiogenesis, etc. Methods: Studies on Endocan and its correlation with cancer were reviewed, and key points of meaningful studies on the structure, pathways and targeted agents of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 56 publications
2
25
0
3
Order By: Relevance
“…In normal tissues, ESM1 is mainly expressed in vascular endothelial cells, distal renal tubular epithelial cells, and pulmonary endothelial cells, and is mainly involved in the in ammatory response [32] and angiogenesis [33]. Accumulative studies have shown that ESM1 was hyper-expressed in a variety of malignancies and was associated with tumor prognosis [34]. In hepatocellular carcinoma, ESM1 was an early-stage biomarker via augmenting the formation of tumor angiogenesis [21].…”
Section: Discussionmentioning
confidence: 99%
“…In normal tissues, ESM1 is mainly expressed in vascular endothelial cells, distal renal tubular epithelial cells, and pulmonary endothelial cells, and is mainly involved in the in ammatory response [32] and angiogenesis [33]. Accumulative studies have shown that ESM1 was hyper-expressed in a variety of malignancies and was associated with tumor prognosis [34]. In hepatocellular carcinoma, ESM1 was an early-stage biomarker via augmenting the formation of tumor angiogenesis [21].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the potential role of both inflammatory cytokines and intercellular adhesion molecules in an inflammatory response and ischemia/reperfusion injuries, it is now hypothesized that the over-expression of endocan can activate both inflammatory and tumoral processing through activation of inflammatory mediators and adhesion molecules. Recent studies have focused on the central role of endocan over-expression in angiogenesis and tumorigenesis and thus this biomarker seems to be a selective target for cancer therapy [16]. This hypothesis has been examined and even demonstrated in subgroups of patients suffering malignancies of liver, kidney, lungs, breast, pancreas, prostate, ovary, and brain glioblastoma [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…1C). All of these genes have been shown to play important roles in tumor progression [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. Interestingly, 8 of these 17 genes have been identified as hypoxia-associated genes, including CA9, gamma-glutamyltransferase 6 (GGT6), KISS1 receptor (KISS1R), enolase 2 (ENO2), hypoxia-inducible lipid droplet-associated protein (HILPDA), EGL-9 family hypoxia inducible factor 3 (EGLN3), endothelial cell specific molecule 1 (ESM1), and NDUFA4 mitochondrial complex-associated like 2 (NDUFA4L2) (Fig.…”
Section: Resultsmentioning
confidence: 99%